Application of Blockchain to Ensure Temper-Proof Data Availability for Energy Supply Chain - Rimsan, M. (Institute of Electrical and Electronics Engineers Inc., 2020)
Energy supply industries play a vital role in a country. Inefficiencies in the energy supply chain regarding tricky contest and the lack of management instantly change energy tariff calculation. This work proposes the Ethereum blockchain platform with existing traditional infrastructure to track and investigate energy supply chain activities using a unique identity with smart contracts. It maintains the records of the organization's activities that are protected and available to stakeholders according to the recognized collection of procedures and practices without requiring any centralized administration. This paper focuses entirely on analyzing and developing a simplified, low-cost economical solution to quickly connect the present energy supply industry at various geological locations to track and trace the linked data in the energy market. Â© 2020 IEEE.